Appropriate Technology Machine Innovation Training for High School-Vocational School Students as an Important Role in Increasing the Productivity of MSMEs in Benowo District - Muharom, Muharom; Kholili, Navik; Nugroho, Alfi; Muchid, Muhammad (Pengabdian Masyarakat dan Inovasi Teknologi (DIMASTEK), 2024)
Empowering appropriate technology is very important to support the sustainability of small businesses in the region. This activity is essential to introduce appropriate technology to high school/vocational school students as young technology drivers. This community service program aims to teach students how to use relevant technology in everyday life. Guiding in completing appropriate technology according to the needs the small business desires properly and correctly. The method for implementing community service activities is carried out by directing the Implementation and completion of the tools used at the regional level. The first stage is developing and applying TTG machines in natural resource management. The second stage is implementing the TTG machine for community empowerment (strategic opportunities and challenges). The third stage is implementing TTG machines to manage abundant natural resource potential. The fourth stage is the promotion of TTG machines for community empowerment in the Implementation of Law No. 6 of 2014. The fifth stage is the design and method of making the TTG machine.